2020
DOI: 10.1080/07391102.2020.1808530
|View full text |Cite
|
Sign up to set email alerts
|

In silico molecular investigations of pyridine N-Oxide compounds as potential inhibitors of SARS-CoV-2: 3D QSAR, molecular docking modeling, and ADMET screening

Abstract: The new coronavirus SARS-CoV-2 virus is causing a severe pneumonia in human, provoking the serious outbreak epidemic CoV-2. Since its appearance in Wuhan, China on December 2019, CoV-2 becomes the biggest challenge the world is facing today, including the discovery of antiviral drug for SARS-CoV-2. In this study, the potential inhibitory of a class of human SARS inhibitors, namely pyridine Noxide derivatives, against CoV-2 was addressed by quantitative structure-activity relationship 3 D-QSAR. The reliable CoM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
(28 reference statements)
0
22
0
2
Order By: Relevance
“…A semiempirical QM/MM DFT calculation of the hydrolytic reaction of M Pro dimer with the fluorogenic substrate Ac-Val-Lys-Leu-Gln-ACC exhibited four transition states, with excellent agreement of computed and experimental ∆G ‡ values [114]. DFT based approaches were applied to a large set of pyridine N-oxide compounds as potential inhibitors of SARS-CoV-2 M Pro , peptidic Michael acceptor compounds, as well as to small molecule Schiff bases [115][116][117]. Moreover, SARS-2 M Pro was virtually screened for inhibition by several hundred natural compounds [118].…”
Section: Mechanisms Of Cysteine Proteasesmentioning
confidence: 99%
“…A semiempirical QM/MM DFT calculation of the hydrolytic reaction of M Pro dimer with the fluorogenic substrate Ac-Val-Lys-Leu-Gln-ACC exhibited four transition states, with excellent agreement of computed and experimental ∆G ‡ values [114]. DFT based approaches were applied to a large set of pyridine N-oxide compounds as potential inhibitors of SARS-CoV-2 M Pro , peptidic Michael acceptor compounds, as well as to small molecule Schiff bases [115][116][117]. Moreover, SARS-2 M Pro was virtually screened for inhibition by several hundred natural compounds [118].…”
Section: Mechanisms Of Cysteine Proteasesmentioning
confidence: 99%
“…ADMET descriptors module in DS include absorption, distribution, metabolism, excretion, toxicity, and other information, which were used to describe and comprehensively analyze the solubility, blood–brain barrier (BBB) penetration, hepatotoxicity, and cytochrome P450 2D6 (CYP2D6) of small molecules in the TCM database. 36,37 In addition, SwissADME 38 was used to judge whether the candidate compounds are the substrates of P-glycoprotein. According to the dock scores, ADMET descriptors results, and the predict results, we selected three possible candidates as the multi-target drugs for AD to perform the subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Continuing their research, the Ghaleb group [ 100 ] found the structural conditions that N-oxides must meet in order to have an increased antiviral activity, which is shown in Figure 23 . In this study, pyridine N-oxide 223 with SARS-CoV inhibitory activity was selected for a further 3 D-QSAR studies.…”
Section: Synthesis Of Antiviral Pyridine Compoundsmentioning
confidence: 99%